Role of Gender Diversity in Organizational Effectiveness and its Implications - Bibi, Naima (International Review of Management and Marketing, 2016)
Even though considerable recognition of women at organizations, quantity of females at managerial positions (middle level and top management level) is increasing, but still too female percentage has a minor increase now a days as they were in the past years. As females are working in a male dominated society and their set procedures and practices, most of the time females face too many hurdles that minimize their pace towards upper level positions in their career growth. Negative perceptions, discrimination and a glass ceiling for females as mangers is the main reason that there is a small number of female executives in organizations. Accordingly, we wonder to know that gender has direct effect on organizational effectiveness and what are the barriers which women face during their professional career growth. This paper is an exploratory research to highlight different type of factors that affect organizational effectiveness and on the true reasons that push back women from proceeding to middle and top positions in organizations. Structured in depth interviews of Top-Level Managers and Focus group of Middle-level Managers were conducted to a convenient sample with the aim of knowing their attitudes and behavior towards role of gender in organizational effectiveness and to recognize its implications that are the reason of biasness, mental block and stereotyping against female at workplace. Keywords: male dominated society, discrimination, glass ceiling, interviews JEL Classifications: J10, M10